Approach to blind synchronization parameters estimation for OFDM systems - GUO Li-ting1; 2 (Tongxin xuebao)
A method for increasing the cyclic period of a cyclostationary signal was first proposed. Then based on it, a cyclostationarity-based, blind algorithm for estimating synchronization parameters in the OFDM system was presented. Finally through analyzing this algorithm, a method was got, which can not only estimate a timing offset which is not an integer multiple of one OFDM sample duration, but also enlarge the frequency offset estimation range, thus, a frequency offset estimation over the entire bandwidth of the OFDM system is possible. Theory analysis and simulation results are provided to show that the proposed algorithm can get more accurate synchronization parameters estimation with few OFDM symbols, meanwhile it is immune to the noise and adapts to the fading channel.